Interactions verbales d'élèves allophones en retard scolaire lors de résolutions collaboratives de problèmes orthographiques - Carole Fleuret; Joël Thibeault (Recherches en didactique des langues et des cultures)
This article explores the verbal interactions among learners who are schooled in French as a second language in Canada during activities of collaborative writing. Once a week for nine weeks, we met with our participants (n=8) for workshops on spelling, and the activities all gravitated around pieces of children's literature. We present here the evolution of their metagraphic comments (Jaffré, 1995) over the course of our nine-week study. The results show that at the beginning of the research, participants focus on the phonogrammic dimension of written French. As the study goes on, they learn to distance themselves from the alphabetic code and, for example, show more cases of lexical evocation. The data which we present here show that verbal interaction can be a strong help for learners during writing activities, that it is important to let them verbalize their representations of the writing system, and that children's literature can be used as a pedagogical tool to improve student spelling.